Tailoring CdO-CuO-ZnO Mixed Metal Oxide Nanocomposites for Anticancer Activity via Co-Precipitation Method - Aziz SN; Abdulwahab AM; Shuga Aldeen T; Ahmed AAA (Nanotechnology, Science and Applications)
Shadha Nasser Aziz,1,2 Abduh Mohammad Abdulwahab,3 Thana Shuga Aldeen,1 Abdullah Ahmed Ali Ahmed3,4 1Physics Department, Faculty of Science, Sana’a University, Sana’a, Yemen; 2Department of Basic Sciences, Al-Darb Community College, Dhamar, Yemen; 3Physics Department, Faculty of Applied Science, Thamar University, Dhamar, 87246, Yemen; 4Fachbereich Physic and Center for Hybrid Nanostructures (Chyn), Universität Hamburg, Hamburg, 22761, GermanyCorrespondence: Shadha Nasser Aziz, Email Shd.Aziz@su.edu.ye Abduh Mohammad Abdulwahab, Email abduhabdulwahab@yahoo.comIntroduction: The use of metal oxide nanoparticles as anticancer agents is of great interest due to their unique properties that allow targeted delivery at low concentrations with minimal toxicity to healthy cells.Methods: In this work, CdO-CuO-ZnO mixed metal oxide nanocomposites were synthesized by the co-precipitation method, and their structural and optical properties, along with their anticancer activity, were investigated. The samples were characterized by X-ray diffraction (XRD), total reflection X-ray fluorescence (TXRF), transmission electron microscopy (TEM), selected area electron diffraction (SAED), UV-Vis spectroscopy, electrometer/high resistance material, and vibrating sample magnetometers (VSM).Results: X-ray diffraction (XRD) measurements showed that CdO exhibits a cubic structure, CuO possesses a monoclinic structure, ZnO displays a hexagonal structure, and the mixture showed peaks corresponding to all three oxides. TEM images revealed that the prepared nanoparticles have quasi-spherical shapes. Anticancer studies confirmed that the CdO-CuO-ZnO nanocomposite demonstrates excellent cytotoxicity, with moderate activity against human colon (Caco-2) and lung (A549) cancer cell lines, exhibiting IC50 values of 10.57 μg/mL and 6.61 μg/mL, respectively.Conclusion: Our study shows that the prepared CdO-CuO-ZnO nanocomposite has massive potential in cancer therapy.Keywords: Co-precipitation, CdO-CuO-ZnO nanocomposite, Anti-cancer activity, Cytotoxic effect